2014
DOI: 10.4049/jimmunol.1303058
|View full text |Cite
|
Sign up to set email alerts
|

RNA and Imidazoquinolines Are Sensed by Distinct TLR7/8 Ectodomain Sites Resulting in Functionally Disparate Signaling Events

Abstract: Toll-like receptors (TLR) 7 and 8 are pattern recognition receptors controlling antiviral host defense or autoimmune diseases. Apart from foreign and host RNA, synthetic RNA oligoribonucleotides (ORN) or small molecules of the imidazoquinoline family activate TLR7 and 8 and are being developed as therapeutic agonists. The structure-function relationships for RNA ORN and imidazoquinoline sensing and consequent downstream signaling by human TLR7 and TLR8 are unknown. Proteome- and genome-wide analyses in primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 46 publications
3
37
0
Order By: Relevance
“…The differential inhibition of bRNA versus small molecule-induced TLR activation might be due to differences in the TLR7/8 binding sites of R848 and RNA, as recently described by Colak et al [42]. They identified overlapping but also non-overlapping binding sites for R848 and RNA40 in the TLR7 and TLR8 ectodomains, resulting in subtle differences in the downstream signalling cascade.…”
Section: Discussionmentioning
confidence: 82%
“…The differential inhibition of bRNA versus small molecule-induced TLR activation might be due to differences in the TLR7/8 binding sites of R848 and RNA, as recently described by Colak et al [42]. They identified overlapping but also non-overlapping binding sites for R848 and RNA40 in the TLR7 and TLR8 ectodomains, resulting in subtle differences in the downstream signalling cascade.…”
Section: Discussionmentioning
confidence: 82%
“…R848 is an imidazoquinoline compound with potent anti‐viral activity and an unrelated TLR8 agonist. R848 and ssRNA40 induce differing signaling cascades downstream of TLR8, with R848 preferentially activating a p38 cascade and ssRNA40 strongly activating ERK (Colak et al , 2014). We examined these signaling cascades in the presence and absence of Snapin knockdown and found that loss of Snapin enhanced phosphorylation of p38 and STAT1 in R848 stimulated DCs, and enhanced phosphorylation of p38 and ERK in ssRNA40 stimulated DCs (Fig 5C and D).…”
Section: Resultsmentioning
confidence: 99%
“…TLR8 can detect HIV‐1 in DCs, as it is required for inducing viral transcription (Gringhuis et al , 2010), but it somehow fails to generate robust anti‐viral cytokine responses (Granelli‐Piperno et al , 2004). TLR8 recognizes ligands such as single‐stranded RNA and imidazoquinolines triggering distinct signaling cascades (Colak et al , 2014) that lead to the activation of interferon‐regulatory factor (IRF)‐dependent interferon responses and NF‐κB‐dependent pro‐inflammatory cytokine responses in DCs. However, the mechanisms by which TLR8 signals in DCs are poorly understood and appear to differ between mice and humans (Ohto et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…MAMPs DAMPs 2 Extracellular Lipopeptide (Takeda et al, 2002) Biglycan (Schaefer et al, 2005), HMGB1 (Yu et al, 2006), HSP60 (Zanin-Zhorov et al, 2003), HSP70 (Vabulas et al, 2002a), human cadiac myosin (Zhang et al, 2009), LMW-HA (Scheibner et al, 2006), MSU crystals (Liu-Bryan et al, 2005), Gp96 (Warger et al, 2006), H␤D-3 (Guo et al, 2013), SPA (Montalbano et al, 2013;Murakami et al, 2002), SPD (Montalbano et al, 2013), EDN , APLAs (Satta et al, 2011), SAA (Cheng et al, 2008) and Versican (Wang et al, 2009) 4 Lipopolysaccharide (Lu et al, 2008) Biglycan (Schaefer et al, 2005), BD-2 (Biragyn et al, 2002;Vora et al, 2004), fibrinogen (Hodgkinson et al, 2008), fibronectin (Okamura et al, 2001), Imidazoquinoline (Colak et al, 2014) and viral ssRNA (Colak et al, 2014;Diebold et al, 2004) ssRNA (Diebold et al, 2004), siRNA (Robbins et al, 2009) and APLAs (Hurst et al, 2009), TLR8 can recognize human cardiac myosin (Zhang et al, 2009) 9 Unmethylated CpG dinucleotides (Takeshita et al, 2001) IgG chromatin complexes (Boulé et al, 2004), DNA (Rutz et al, 2004) and HMGB1 (Ivanov et al, 2007) as receptors for yet-to-be discovered DAMPs. In addition, DAMPs such as HMGB1 exhibit the potential to interact with multiple TLRs in different cells (Apetoh et al, 2007;Tang et al, 2007a;Tian et al, 2007).…”
Section: Tlr Membrane Localizationmentioning
confidence: 98%